Oficjalna strona internetowa jako narzędzie kreowania wizerunku głowy państwa w Polsce, Rosji i Wielkiej Brytanii: The official website as a tool for creating the image of the head of state in Poland, Russia and the United Kingdom - Noińska, Marta (Przegląd Wschodnioeuropejski, 2020)
The paper analyzes the role of official websites in creating the image of the head of state in Poland, Russia and the United Kingdom. The official website is a convenient tool allowing not only the appropriate presentation of the leader, but also the immediate publication of new content. The wide variety of semiotic resources used on the webpages attracts and maintains the attention of the recipient. The author describes the history of the official websites, identifies the genres characteristic of individual political cultures and observes similarities and differences related to the image of the current head of state.